PENGARUH PENERAPAN STRATEGI GENIUS LEARNING DENGAN OPERAN KERTAS IDE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA BAITURRAHMAH PADANG - Berlina, Nina - (Pendidikan Biologi, 2014)
Background of this research was low obtained result of study biologi students on the ecosystem and environmental pollution. This problem were coused by the interaction in the learning process just one direction only from the teacher to the students. Interaction between students and teacher also not much, so that they do not have a mutual relationship. This result make students inclined to feel borted and less motivated to the material presented by the teacher. Overcome this problems the writer used Genius Learning whit operan kertas ide toward result of biology learning for studen class X SMA Baiturrahmah Padang. The kind of this research is experimental research. Population in this research are all of the students in the class X SMA Baiturrahmah Padang, listed in the school year 2013/2014. The research design used a randomized control group postest only design. Based on the analysis of the obtained average value of the experimental class is 75,39 and class control is 69,16. Hypothesis test used t-test values obtained =1,54 > =0,161, it means that the strategy of learning by using Genius Learning with operan kertas ide can increase learning biology class X SMA Baiturrahmah Padang.